SIFAT ANATOMI KAYU JABON (Anthocephalus cadamba) DARI BEBERAPA LOKASI DI INDONESIA - Supitra, Alpian; susdiyanti, Tun; Rusli, Abdul Rahman; Krisdyanto, Krisdyanto (Jurnal Nusa Sylva, 2024)
Jabon wood (Anthocephalus cadamba Miq.) Is one of Indonesia's native forest plant species that is potential to be cultivated as timber plantation and pulpwood. jabon wood easy to work, soft and light, white cream color to reddish brown, glowing and slightly porous with average gravity of 0.42 or ranged from 0.29 to 0.56. Has a strong class III (medium) and durable class IV to V. This study uses the method of observation with data analysis done by using descriptive and quantitative analysis. The results showed macroscopic and microscopic analysis on 7 timber which meticulously vary in texture, vessel diameter, velocity frequency, radius radius radius, and noktah. The 7 samples were compared based on the general characteristics of jabon wood anatomy.